2015
DOI: 10.1002/pssb.201552264
|View full text |Cite
|
Sign up to set email alerts
|

Polar and semipolar (112) InAlN layers grown on AlN templates using MOVPE

Abstract: We report on metalorganic vapor phase epitaxial growth of InAlN layers on (0001) and (11true2‾2) AlN templates at different temperatures (725–800 °C). The indium content (8.0–15.2%) of the (11true2‾2) InAlN layers was found to be lower compared to that for the (0001) layers (9.0–23.0%). The higher indium content of the (0001) layers was attributed to a high density of small hillocks and a larger degree of relaxation. The small hillocks on the (0001) layer surface acted as quantum‐dot‐like structures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 29 publications
5
13
0
Order By: Relevance
“…Figure 6 shows an SEM image of In 0.8 Al 0.2 N(1 103) grown on InN(1 103)/YSZ(113). Striations along the direction perpendicular to InAlN [11 20] are observed, which are similar to those on semipolar InAlN surfaces grown by other techniques [18,19].…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Figure 6 shows an SEM image of In 0.8 Al 0.2 N(1 103) grown on InN(1 103)/YSZ(113). Striations along the direction perpendicular to InAlN [11 20] are observed, which are similar to those on semipolar InAlN surfaces grown by other techniques [18,19].…”
supporting
confidence: 61%
“…However, semipolar growth of InAlN suffers from two main obstacles, namely, lack of suitable substrates and immiscibility between InN and AlN . Consequently, there are only a few reports on growth of semipolar InAlN films . The former issue can be overcome by utilizing yttria‐stabilized zirconia (YSZ) which possesses lattice match with high In‐content InAlN; thus, it is a promising candidate for growing high In‐content semipolar InAlN.…”
Section: Introductionmentioning
confidence: 99%
“…This information is consistent with the surface observation results shown in Figure 2. Then, the TEM images also revealed that the BSFs in the GaN (0001) plane, [ 29,30 ] which are observed as lines parallel to the [ 11 2 ¯ 0 ] direction, propagated up to the top AlInN layer through the GaInN layer. This information agrees with the result of the XRD‐RSMs shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the existence of basal-plane stacking faults (BSFs) in the (0001) lattice planes. [29,36] On the other hand, the diffraction peaks from AlInN layers were observed to greatly broaden along the TEM study was carried out to analyze their crystal mosaicity in more detail.…”
Section: Xrd Analysesmentioning
confidence: 99%
See 1 more Smart Citation